New Tendencies in Higher Education in the Knowledge Society - Văcărescu - Hobeanu, Loredana (Journal of Research in Educational Sciences, 2011)
An expressive feature of the globalization is the reliance on knowledge, which is focused on the increasing of the role of human capital, focusing on the efficiency gains on educated and specialized human resources, on the closer connection between knowledge and competitiveness. The knowledge-based society is characterized by dynamism and continuous renewal. The complexity of the phenomena from the modern society requires an increasingly richer stock of knowledge and skills. Our society currently confronts with the consequences of a financial and global crisis. To improve and develop in a durable way the existing economy, the dynamic and flexible higher education will rely on innovation which is based on the integration between education and research at all levels. The higher education plays a key role in the confronting with the current challenges and the promotion of the cultural and social development of our society.